The Effects of Different Doses of Caudal Morphine with Levobupivacaine on Postoperative Vomiting and Quality of Analgesia after Circumcision. Issue 2 (March 2014) - Dostbil, A.; Celik, M. Gursac; Aksoy, M.; Ahiskalioglu, A.; Celik, E. C.; Alici, H. A.; Ozbey, I.
The study aim was to investigate the effect of three different morphine doses added to levobupivacaine 0.125% for caudal analgesia after circumcision surgery in children, particularly in relation to the frequency of postoperative vomiting within the first 24 hours following surgery. Two hundred and forty patients aged 5 to 12 years undergoing circumcision were included in the study. Following induction, caudal 0.125% levobupivacaine 0.5 ml/kg was given after adding 7.5, 10 or 15 μg/kg morphine. The postoperative incidence of vomiting was 5%, 12.5% and 17.5% in the groups 7.5, 10 and 15 μg/kg morphine, respectively ( P =0.012, 7.5 versus 15 μg/kg groups). Five percent of the 7.5 μg/kg group and none of the patients in the other groups required paracetamol within the first 12 hours, and there was a significantly greater need for rescue paracetamol over the 24 hours in the 7.5 group versus the 15 μg/kg group ( P =0.013). Postoperative analgesic durations were long and did not differ between groups (1273±338, 1361±192 and 1426±48 minutes, respectively, P =0.08). In conclusion, because the incidence of vomiting is very low, the duration of postoperative analgesia is long and a dose of 7.5 μg/kg caudal morphine is much lower than doses previously reported to be associated with respiratory depression, this study supports the use of 7.5 μg/kg caudal morphine added to 0.125% levobupivacaine for circumcision surgery.